2008
DOI: 10.1097/wnr.0b013e328318ed9a
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol inhibits voltage-gated sodium channels in cultured superior cervical ganglion neurons

Abstract: To determine whether actions on sodium channels contribute to ethanol's depressant effects on the autonomic nervous system, the acute effects of ethanol on Na+ currents in primary cultured superior cervical ganglion were examined by whole-cell patch clamp recordings. Ethanol inhibited Na+ currents concentration dependently, and decreased action potential firing. Ethanol (100 mM) did not affect activation curve, but resulted in a left shift of the inactivation curve and prolonged the recovery from inactivation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…We also demonstrated that EtOH at high concentrations (100 or 300 mM) inhibited the voltage-dependent Na ϩ and Ca 2ϩ currents (I Na and I Ba ). Again, these findings concur with results obtained from rat hippocampal slices (Hendricson et al, 2004), cultured superior cervical ganglion neurons (Xiao et al, 2008), and recombinant channels expressed in Xenopus laevis oocytes (Horishita and Harris, 2008). However, such high concentrations of EtOH are beyond those typically encountered by social drinkers and, in fact, bring a significant risk of death.…”
Section: Gaba a Receptors On Inhibitory And Excitatory Nerve Terminalsupporting
confidence: 76%
“…We also demonstrated that EtOH at high concentrations (100 or 300 mM) inhibited the voltage-dependent Na ϩ and Ca 2ϩ currents (I Na and I Ba ). Again, these findings concur with results obtained from rat hippocampal slices (Hendricson et al, 2004), cultured superior cervical ganglion neurons (Xiao et al, 2008), and recombinant channels expressed in Xenopus laevis oocytes (Horishita and Harris, 2008). However, such high concentrations of EtOH are beyond those typically encountered by social drinkers and, in fact, bring a significant risk of death.…”
Section: Gaba a Receptors On Inhibitory And Excitatory Nerve Terminalsupporting
confidence: 76%
“…Although not tested here, ethanol, at concentrations similar to that used as a positive control in the stopped-flow bilayer experiments (see below and Fig. 5 ), also inhibits I Na ( Frenkel et al, 1997 ; Wu and Kendig, 1998 ; Klein et al, 2007 ; Horishita and Harris, 2008 ; Xiao et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Subthreshold Na + currents, active at voltages between -60 and –70 mV, were detected in rat GoCs and these likely contribute to the generation of the slow pacemaker depolarization preceding the spike threshold (Forti et al, 2006). Several studies have shown that ethanol acutely inhibits or has no effects on Na + channels but we are not aware of any studies on subthreshold Na + channels (Habuchi et al, 1995, Shiraishi and Harris, 2004, Klein et al, 2007, Xiao et al, 2008, Horishita and Harris, 2008, Searl and Silinsky, 2010). Evidence suggests that a specialized, non-inactivating subtype of Na + channels of unknown molecular characteristics mediates subthreshold currents (Taddese and Bean, 2002, Crill, 1996, Bean, 2007).…”
Section: Discussionmentioning
confidence: 95%